Adolescents' Perspectives on Vaccination Outside the Traditional Medical Home: A Survey of Urban Middle and High School Students. (April 2013) - Pyrzanowski, Jennifer; Curtis, C. Robinette; Crane, Lori A.; Barrow, Jennifer; Beaty, Brenda; Kempe, Allison; Daley, Matthew F.
Eleventh- and 6th-grade students from an urban public school district were surveyed concerning vaccination outside the traditional medical home. Survey response rates were 50% for 11th- and 73% for 6th-grade students. Seventy-two percent of 11th-grade students reported that public health clinics were definitely or probably acceptable locations for vaccination; 70% reported this for emergency departments, 65% for school-based health centers, 55% for family planning clinics, and 44% for obstetrics/gynecology clinics. Corresponding percentages for 6th-grade students were 60% for public health clinics, 49% for emergency departments, 39% for school-based health centers, and 36% for family planning clinics. Sixth-grade students were not asked about obstetrics/gynecology clinics. Forty-seven percent of respondents identified a doctor's office as the "best" setting to receive vaccines, more than identified any other setting. We concluded that vaccination in one or more settings outside the traditional medical home was acceptable to most adolescents.